"How Do I Deal with Burnout?". (1st April 2021) - Newton, Richard
Abstract : In this edition of the Bulletin for the Study of Religion's advice column, Sage D'Vice answers helps readers deal with burnout. The piece emphasizes scholars' need to understand their situatedness within a variety of settings and the ways they can use their skills effectively to negotiate the demands of those settings. Sage D'Vice offers practical tips to help scholars build upon their strengths, manage service expectations, and maximize their productivity.